Perception of teacher role in Chinese high schools in Manila - Ng, Fe P. 1922-
The purpose of the study is to determine the teacher's roles in Chinese secondary schools in the City of Manila as perceived by the teachers themselves, their administrators, and the students. Findings of the study reveal that all respondents regarded Role V: The teacher's role as a liason between school and community least important. Of all the respondents, the English teachers gave the highest index values to all roles (The teacher's role as a mediator of culture, member of a profession, director of learning, member of school community, and liason between school and community). The administrators and the Chinese teachers gave moderate index values while the students gave the lowest index values.